Negosiasi Identitas Kristen-Katolik Di Kecamatan Kamal, Bangkalan-Madura - Vina Amalia; Agustinus Raja Dasion (Journal of Social, Culture, and Language, 2023)
Religions were born in an effort to build a prosperous, peaceful society and provide motivation and inspiration for humans to build a high civilization by promoting human values and ideals. Although each religion has its own belief in God and worldview. Sometimes they claim that they are the only truth. In this case the researcher wants to explain the relationship between Muslims and Catholics in Madura, especially in Kamal sub-district, Bangkalan district - Madura. Considering the stereotypes of Madurese people who are violent and fanatical in religion. Therefore, the urgency of the problem of this research arises, which includes how the Christian-Catholic identity negotiation in Kamal District, so that its religious adherents can be well accepted by the local community. And how the relationship built by Christian-Catholic adherents in Kamal District, Bangkalan Madura Regency. The author tries to describe the above phenomenon by analyzing Tajfel and Turner's Social Identity Theory. The author studies with an ethnographic research method approach. Basically, the inherent nature of ethnographic research is holistic-integrative. It is intended to be able to provide an overall explanation, which consists of parts that cannot be separated. Therefore, it can be said that the interaction of the parts of culture has merged. Keywords: Identity Negotiation, Relationship, Catholics, Kamal